Lubricating oil composition

The lubricating oil composition, featuring coated nanoparticles with phosphonic acid, addresses the need for higher lubricity in automotive parts, significantly reducing friction and enhancing energy efficiency.

JP7653235B2Active Publication Date: 2025-03-28SHELL LUBRICANTS JAPAN KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020150804
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-08
Publication Date
2025-03-28
Estimated Expiration
2040-09-08

AI Technical Summary

Technical Problem

Existing lubricating oil compositions, despite reducing friction, do not meet the increasing demand for higher lubricity to enhance energy efficiency in automotive parts.

Method used

A lubricating oil composition is developed that includes a base oil and coated particles consisting of nanoparticles and phosphonic acid, where the phosphonic acid coats at least a portion of the nanoparticle surface, improving lubricity.

Benefits of technology

The composition achieves excellent lubricity, enhancing energy efficiency by reducing friction in automotive parts, thereby meeting the growing demand for energy-saving solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653235000001
    Figure 0007653235000001
  • Figure 0007653235000002
    Figure 0007653235000002
Patent Text Reader

Abstract

To provide a lubricant composition having excellent lubricity.SOLUTION: The lubricant composition comprises: a base oil; and coated particles consisting of nanoparticles and phosphonic acid that coats at least a portion of a surface of the nanoparticles.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lubricating oil composition. [Background technology]

[0002] In order to improve the fuel efficiency of automobile parts, etc., it is important to prevent energy loss due to friction in the engine during automobile operation. That is, in order to improve fuel efficiency, it is effective to use a lubricating oil composition that reduces the friction coefficient of sliding parts.

[0003] As such a lubricating oil composition, Patent Document 1 discloses a lubricating oil composition containing a base oil, an oxygen-containing organic compound, diamond nanoparticles, and a dispersant for diamond nanoparticles. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-179738 A

[0005] The lubricating oil composition according to the cited document 1 makes it possible to significantly reduce the coefficient of friction, but due to the increasing demand for energy conservation, even higher lubricity is required. Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the above problems, an object of the present invention is to provide a lubricating oil composition having excellent lubrication properties. [Means for solving the problem]

[0007] The present inventors have found that extremely excellent lubricity can be obtained by blending specific particles in a lubricating oil composition, and have completed the present invention.

[0008] The present invention relates to The lubricating oil composition comprises a base oil, nanoparticles, and coated particles made of phosphonic acid that coat at least a portion of the surface of the nanoparticles. The nanoparticles may be a metal oxide. The surface coverage of the coated particles with the phosphonic acid may be 10% or more.

[0009] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: Particles added to a lubricating oil composition comprising a base oil, The lubricating oil composition additive particles may be characterized as being coated particles comprising nanoparticles and a phosphonic acid coating the surfaces of the nanoparticles. Effect of the Invention

[0010] According to the present invention, it is possible to provide a lubricating oil composition having excellent lubricity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The composition, physical properties / characteristics, production method and applications of the lubricating oil composition will be described below, but the present invention is not limited to these.

[0012] <<<Composition of lubricating oil composition>>> The lubricating oil composition includes a base oil and the coated particles. The lubricating oil composition may also include other components.

[0013] <<Base oil>> The base oil is not particularly limited and can be appropriately changed depending on the application of the lubricating oil composition. As the base oil, mineral oil, synthetic oil, animal and vegetable oil, and mixed oils thereof used in ordinary lubricating oil compositions can be appropriately used. Specific examples of the base oil include base oils belonging to Group 1, Group 2, Group 3, Group 4, etc. in the API (American Petroleum Institute) base oil category. Only one type of base oil may be used, or two or more types may be used.

[0014] Group 1 base oils include, for example, paraffinic mineral oils obtained by applying an appropriate combination of refining means such as solvent refining, hydrorefining, and dewaxing to a lubricating oil fraction obtained by atmospheric distillation of crude oil. Group 2 base oils include, for example, paraffinic mineral oils obtained by applying an appropriate combination of refining means such as hydrocracking and dewaxing to a lubricating oil fraction obtained by atmospheric distillation of crude oil. Group 2 base oils refined by hydrorefining methods such as the Gulf method have a total sulfur content of less than 10 ppm and an aromatic content of 5% or less, and can be suitably used in the present invention. Group 3 base oils and Group 2 plus base oils include, for example, paraffinic mineral oils produced by advanced hydrorefining of a lubricating oil fraction obtained by atmospheric distillation of crude oil, base oils refined by the ISODEWAX process in which wax produced in the dewaxing process is converted and dewaxed into isoparaffins, and base oils refined by the MobilWAX isomerization process.

[0015] Examples of synthetic oils include polyolefins, diesters of dibasic acids, triesters of trimellitic acid, polyol esters, alkylbenzenes, alkylnaphthalenes, and esters. , polyoxyalkylene glycol, polyoxyalkylene glycol ester, polyoxyalkylene glycol ether, polyphenyl ether, dialkyl diphenyl ether, fluorine-containing compounds (perfluoropolyether, fluorinated polyolefin, etc.), silicone, etc. The polyolefin includes various olefin polymers or hydrogenated products thereof. Any olefin may be used, and examples thereof include ethylene, propylene, butene, and α-olefins having 5 or more carbon atoms. In producing the polyolefin, one of the olefins may be used alone, or two or more of them may be used in combination.

[0016] Base oil obtained by GTL (gas-to-liquids) synthesis using the Fischer-Tropsch process, a technology for converting natural gas into liquid fuel, has extremely low sulfur and aromatic contents and an extremely high paraffin composition ratio compared to mineral oil base oil refined from crude oil, and therefore has excellent oxidation stability and very small evaporation loss, making it suitable for use as the base oil in this embodiment.

[0017] The base oil has a KV100℃ (kinetic viscosity at 100℃) of 1.0 to 10 mm 2 / s, and 1.5 to 5.0 mm 2 / s is more preferable, and 1.7 to 3.0 mm 2 By using such a base oil (particularly a GTL base oil), it is possible to improve lubricity.

[0018] The content of the base oil in the entire lubricating oil composition can be 50 mass% or more, 60 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, 95 mass% or more, 97 mass% or more, or 99 mass% or more, etc.

[0019] <<Coated particles>> The coated particles are nanoparticles in which at least a part of the surface is coated with phosphonic acid. In other words, the coated particles can be expressed as nanoparticles having phosphonic acid fixed to the surface.

[0020] The coated particles can be produced by contacting nanoparticles with phosphonic acid. The time and temperature for contacting the nanoparticles with phosphonic acid can be appropriately changed. In addition, in order to facilitate the immobilization of phosphonic acid on the nanoparticle surface, the nanoparticles may be subjected to a surface treatment in advance.

[0021] The coated particles may be present as secondary particles (aggregates) in the composition. The average particle size of the coated particles, taking into account the secondary particles, is, for example, 5 to 1500 nm, 5 to 500 nm, 20 to 200 nm, 50 to 100 nm, etc. The average particle size of the primary particles of the coated particles is the same as the average particle size of the nanoparticles.

[0022] The content of the coated particles in the entire lubricating oil composition is preferably 0.01 to 5 mass %, more preferably 0.02 to 3 mass %, and even more preferably 0.05 to 0.5 mass %.

[0023] By using nanoparticles whose surfaces are coated with phosphonic acid, the dispersibility in the base oil is improved by making the particles hydrophobic, and the particles can penetrate into the sliding surface, thereby improving lubricity.

[0024] <Nanoparticles> The material of the nanoparticles is not particularly limited and may be either inorganic (e.g., metal, metal compound, carbon, etc.) or organic (e.g., pigment, etc.), but is preferably inorganic, and more preferably a metal oxide. Examples of metal oxides include nickel oxide, cobalt oxide, manganese oxide, aluminum oxide, titanium oxide, copper oxide, iron oxide, zinc oxide, silicon oxide, etc., but is preferably aluminum oxide or titanium oxide. Only one type of nanoparticle may be used, or two or more types may be used.

[0025] The average particle size of the nanoparticles is preferably 1 to 1000 nm, more preferably 5 to 500 nm, even more preferably 5 to 100 nm, and particularly preferably 10 to 100 nm. The average particle size of the nanoparticles can be measured using a dynamic light scattering (DLS) measuring device at a measurement time of 120 seconds and a measurement temperature of 60°C. (Reference for measurement principle: https: / / unit.aist.go.jp / rima / nanoscp / coms / nano / dls.html).

[0026] The shape of the nanoparticles is usually spherical, but may be other shapes (eg, plate-like, rod-like, needle-like, scale-like, tubular, irregular, etc.).

[0027] The content of the nanoparticles in the entire lubricating oil composition is preferably 0.01 to 5 mass %, more preferably 0.02 to 3 mass %, and even more preferably 0.05 to 0.5 mass %.

[0028] <Phosphonic acid> The phosphonic acid is not particularly limited as long as it is a compound containing one or more structures represented by [-P(=O)(OH)2] (preferably a compound containing one), but for example, butylphosphonic acid, octylphosphonic acid, decylphosphonic acid, dodecylphosphonic acid, undecylphosphonic acid, (3-carboxypropyl)phosphonic acid, 3-bromopropanephosphonic acid, (2-hydroxyethyl)phosphonic acid, (2-phenylethyl)phosphonic acid phenethylphosphonic acid, 10-hydroxydecylphosphonic acid, 10-(ethoxycarbonyl)decylphosphonic acid, 2-phosphonobutane-1,2,4-tricarboxylic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotrimethylenephosphonic acid, ethylenediaminetetramethylenephosphonic acid, etc. may be used. Only one type of phosphonic acid may be used, or two or more types may be used.

[0029] The surface coverage of the coated particles with phosphonic acid is preferably 10% or more, more preferably 15% or more, and more preferably 17% or more. The surface coverage may be 100%, 90% or less, 80% or less, or 75% or less. By setting the surface coverage of the coated particles in such a range, the lubricity can be improved. The surface coverage of the coated particles can be calculated using elemental analysis of the coated particles and the area occupied by the phosphonic acid that covers the surface. Specifically, it is as follows.

[0030] The elemental analysis of the nanoparticles coated with organic phosphonic acid is carried out by ICP-AES measurement. For the measurement, a Varian VISTA-MPX spectrometer manufactured by VARIAN, etc. can be used. As a pretreatment for elemental analysis, the measurement sample is heated in a mixed solution of ammonium sulfate, sulfuric acid, and nitric acid in stages at 200, 250, 300, and 350°C for 30 minutes each, and after cooling, hydrochloric acid is added and heated at 150°C for 20 minutes, and then the sample solution is made constant volume with pure water. As an example, a case will be described in which the nanoparticles are alumina (Al2O3) and the phosphonic acid group of the organic phosphonic acid is monovalent. The measured elements are Al (aluminum) and P (phosphorus), and Y (yttrium) is used as the internal standard. The respective concentrations are determined using the calibration curve method, and the molar ratio x [-] of P to Al is calculated from the atomic weights of each, giving a molar ratio of 2x [-] for the organic phosphonic acid modified on alumina Al2O3. The molar amount of the organic phosphonic acid modified on 1 g of alumina Al2O3 (formula weight: 101.96 [g / mol]) is calculated to be 2x / 101.96 [mol], and the number of molecules of the modified organic phosphonic acid is calculated to be the Avogadro constant N A Using this, it is calculated as 2NAx / 101.96 [numerator]. Assuming that all of the alcohol moieties of the organic phosphonic acid react with the particle surface and are immobilized tridentately, the area occupied by the organic phosphonic acid modified on the surface of 1 g of alumina nanoparticles is 0.24 [nm 2 [References], (2NAx / 101.96) × 0.24 [nm 2 ] is calculated. On the other hand, the surface area of ​​1 g of alumina nanoparticles is the specific surface area A [nm 2 / g]. A Microtrac BELSORP mini II or the like can be used for the measurement. Therefore, the surface coverage is {(2N A x / 101.96) × 0.24} / A × 100[%]. [Cited documents] Alberti, G.; Casciola, M.; Costantino, U.; Vivani, R. Layered and pillared metal(IV) phosphates and phosphonates. Adv Mater 1996, 8, 291-303. DOI:10.1002 / adma.19960080405

[0031] The surface coverage of the coated particles can be adjusted by changing the contact conditions between the nanoparticles and the phosphonic acid (particularly, the mixing ratio of the nanoparticles and the phosphonic acid).

[0032] <<Other ingredients>> As the other components, for example, additives that can be usually blended in lubricating oil compositions can be blended. Such additives include dispersants, detergents, antiwear agents, metal deactivators, antioxidants, antifoaming agents, etc. As the other components, only one type may be used, or two or more types may be used.

[0033] The lubricating oil composition preferably contains a dispersant, more preferably contains an amine-based dispersant. By blending such a dispersant, the precipitation of the coated particles can be prevented and high lubricity can be achieved. Examples of the amine-based dispersant include polyamine-based compounds such as polyolefin polyamine succinimide.

[0034] The content of other components in the entire lubricating oil composition may be the remainder excluding the base oil and the coated particles, and may be, for example, 30 mass% or less, 20 mass% or less, 10 mass% or less, 5 mass% or less, 3 mass% or less, or 1 mass% or less.

[0035] When the lubricating oil composition contains a dispersant, the content of the dispersant relative to the entire lubricating oil composition is preferably 0.1 to 10 mass%, more preferably 0.2 to 5 mass%, and even more preferably 0.5 to 3 mass%.

[0036] <<<Physical properties of lubricating oil compositions>>> <<Kinematic viscosity>> The 40°C kinematic viscosity of the lubricating oil composition is 1 to 50 mm 2 / s, and 2 to 25 mm 2 / s is more preferable, and 4 to 10 mm 2 The lubricating oil composition preferably has a kinematic viscosity at 100°C of 0.5 to 10 mm / s. 2 / s is preferably 0.8 to 8 mm 2 / s is more preferable, and 1 to 5 mm 2 It is more preferable that the ratio is / s.

[0037] <<density>> The density of the lubricating oil composition is 0.1 to 2.0 g / cm 3 is preferably 0.5 to 1.5 g / cm 3 and preferably 0.7 to 1.1 g / cm 3 It is more preferable that:

[0038] <<<Method of manufacturing lubricating oil composition>>> There are no particular limitations on the method for producing the lubricating oil composition, and the composition can be produced by mixing the base oil, the coated particles, and, if necessary, other additive components.

[0039] In addition to the above-mentioned methods, another example of a method for producing a lubricating oil composition is to mix a base oil, nanoparticles, and a phosphonic acid, bring the nanoparticles and the phosphonic acid into contact with each other in the base oil, and form coated particles in the base oil, thereby producing a lubricating oil composition.

[0040] <<<Uses of lubricating oil compositions>>> Since the lubricating oil composition has excellent lubricating properties, it can be used in any application in which it is interposed between members having sliding surfaces, but it is preferable to use it in transmissions, internal combustion engines, etc. Examples of transmissions include gear devices, CVTs, ATs, MTs, DCTs, etc. EXAMPLES

[0041] EXAMPLES Next, the present invention will be described more specifically with reference to examples and comparative examples, but the present invention is not limited to these examples in any way.

[0042] <<<Raw materials>>> <<Base oil>> GTL base oil (KV100℃: 1.9mm 2 / s)

[0043] <<Nanoparticles>> Spherical Alumina Particles The average particle size (average primary particle size) is 30 to 60 nm. The average particle size in the composition is given in the table.

[0044] <<Phosphonic acid>> <Phosphonic acid A> Dodecylphosphonic acid (terminal alkyl phosphonic acid) <Phosphonic acid B> 10-Hydroxydecylphosphonic acid (terminal alcohol phosphonic acid) <Phosphonic acid C> 11-Phosphonoundecyl acid (terminal carboxylic acid phosphonic acid)

[0045] <<Dispersant>> Amine-based dispersant (OLOA 11016, manufactured by Chevron Japan Co., Ltd.)

[0046] <<<Manufacturing of coated particles>>> The coated particles were produced by contacting the nanoparticles with phosphonic acid. Table 1 shows the type of phosphonic acid used in producing the coated particles and the coverage of the coated particles. The surface coverage of the coated particles was adjusted by changing the mixing ratio of the nanoparticles and phosphonic acid. Nanoparticle D was not coated with phosphonic acid, and the above-mentioned nanoparticles were used as they were.

[0047] [Table 1]

[0048] <<<Manufacture of lubricating oil composition>>> Lubricating oil compositions were obtained by mixing the components in the amounts (mass%) shown in Table 2. In Comparative Example 4, no nanoparticles were added, and the same amount of phosphonic acid A as the amount of phosphonic acid A immobilized on nanoparticles A was added. In Comparative Example 5, no nanoparticles were added, and phosphonic acid A was added in an amount 20 times the amount of phosphonic acid A immobilized on nanoparticles A.

[0049] The density of the lubricating oil composition of each example is 0.7 to 1.1 g / cm 3 The 40°C kinematic viscosity of the lubricating oil composition of each Example was in the range of 6.0 mm. 2 / s, and the kinetic viscosity at 100°C is 2.0mm 2 / s.

[0050] <<<Evaluation>>> <<Lubricity test>> The lubricity was evaluated by a friction coefficient test using an MTM testing machine.

[0051] <Evaluation method> The test used a steel ball rolling and sliding on a steel disc. In the standard configuration, the ball was loaded against the face of the disc and the ball and disc were driven independently to create mixed rolling / sliding contact. A force transducer measured the friction force between the ball and disc. Additional sensors measured the load, lubricant temperature, and (in some cases) the electrical contact resistance between the samples and the relative wear between them.

[0052] Before the test, the ball and the disk were immersed in the lubricant composition, which was heated to 60° C. Then, the coefficient of friction was measured by changing the speed at a fixed sliding-rolling ratio under the following test conditions:

[0053] Test piece (disc): PCS standard steel disc (AISI52100, Ra0.02μm) Test piece (ball): PCS standard steel ball with hole (AISI52100, Ra0.02μm) Ball radius: 0.95cm

[0054] (Break-in conditions) Maximum Hertzian pressure: 1.0GPa Lubricant temperature: 60℃ Entrainment speed: 1000mm / s Slip-to-roll ratio (SRR): 0%

[0055] (Test conditions) Maximum Hertzian pressure: 1.0GPa Lubricant temperature: 60℃ Ball radius: 0.95cm Entrainment speed: 1~3000mm / s Slip-to-roll ratio (SRR): 40%

[0056] The slip-roll ratio (SRR) is the ratio of the sliding speed (U ボール -U ディスク ) and entrainment velocity (U ボール +U ディスク ) / 2.

[0057] <Evaluation criteria> ◎: Friction reduction rate at 100mm / s is 20% or more ○: Friction reduction rate at 100mm / s is less than 10-20% ×: Friction reduction rate at 100mm / s is 0-10% or less

[0058] [Table 2]

Claims

1. A lubricating oil composition comprising a base oil, nanoparticles and coated particles comprising a phosphonic acid that coats at least a portion of the surface of the nanoparticles, the surface coverage of the coated particles with the phosphonic acid is 10% or more; the content of the coated particles relative to the total amount of the lubricating oil composition is 0.02 to 3 mass %, The lubricating oil composition, wherein the nanoparticles are aluminum oxide or titanium oxide.

2. Particles added to a lubricating oil composition comprising a base oil, A coated particle comprising a nanoparticle and a phosphonic acid coating a surface of the nanoparticle, the surface coverage of the coated particles with the phosphonic acid is 10% or more; The nanoparticles are aluminum oxide or titanium oxide.

Citation Information

Patent Citations

  • Solvent-free silica nanofluid and application thereof

    CN108085089A

  • Lubricant composition

    JP2008179738A

  • Lubricating oil and method for manufacturing the same, engine and bearing using them, and machinery

    JP2010024318A

  • Lubricant composition

    JP2020180248A

  • Lubricant composition

    JP2020180249A